Development of an IoT-Monitoring and Control System for Solar Panel Surface Temperature Regulation Utilizing Water-Cooling Techniques - Ariadita, Silfia Cindy; Ma'arif, Alfian (Peneliti Teknologi Teknik Indonesia, 2023)
As the world's energy needs escalate and the availability of finite natural resources diminishes, there is an urgent need to explore sustainable alternatives. Renewable energy sources, including solar power, hold great promise due to their abundance, cost-effectiveness, and environmental friendliness. Solar panels, a cornerstone of renewable energy, have the potential to provide clean electricity, but their efficiency depends on temperature control. This research addresses this challenge by implementing an Internet of Things (IoT) monitoring and control system using the Blynk platform to regulate solar panel surface temperatures. The system's smart design uses water pumps to mitigate excessive temperatures, improving performance and energy efficiency. Extensive testing demonstrated the system's effectiveness, particularly in mitigating temperature spikes, improving system efficiency and sustainability. Our results demonstrate the remarkable potential of water-cooled systems and IoT technology to revolutionize solar energy harvesting, marking a significant step toward a sustainable energy future.